Towards a population-based threshold of protection for COVID-19 vaccines. Issue 2 (21st January 2022) - Goldblatt, David; Fiore-Gartland, Andrew; Johnson, Marina; Hunt, Adam; Bengt, Christopher; Zavadska, Dace; Snipe, Hilda Darta; Brown, Jeremy S.; Workman, Lesley; Zar, Heather J.; Montefiori, David; Shen, Xiaoying; et al.
Abstract: Correlates of protection for COVID-19 vaccines are urgently needed to license additional vaccines. We measured immune responses to four COVID-19 vaccines of proven efficacy using a single serological platform. IgG anti-Spike antibodies were highly correlated with ID50 neutralization in a validated pseudoviral assay and correlated significantly with efficacies for protection against infection with wild-type, alpha and delta variant SARS-CoV-2 virus. The protective threshold for each vaccine was calculated for IgG anti-Spike antibody. The mean protective threshold for all vaccine studies for WT virus was 154 BAU/ml (95 %CI 42–559), and for studies with antibody distributions that enabled precise estimation of thresholds (i.e. leaving out 2-dose mRNA regimens) was 60 BAU/ml (95 %CI 35–102). We propose that the proportion of individuals with responses above the appropriate protective threshold together with the geometric mean concentration can be used in comparative non-inferiority studies with licensed vaccines to ensure that new vaccines will be efficacious.